The dragons of Eden : speculations on the evolution of human intelligence - Sagan, Carl, 1934-1996 (New York : Ballantine Books, 1980)
The well-known astronomer and astrobiologist surveys current knowledge of the development of intelligence on Earth in various forms of life and explains his persuasion that intelligence must have developed along similar lines throughout the universe.
Includes index and bibliography : pages [241]-249.
Keywords: Genetic psychology; Brain; Intellect; Evolution